Hipogram dalam Makna Paqjappi pada Masyarakat Bugis Desa Panyula Kabupaten Bone: Kajian Semiotika Riffaterre - Sulastri, Sulastri; M, Asia; Saguni, Suarni Syam (TITIK DUA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2024)
This study aims to examine the meaning of paqjappi used in Bugis traditional medicine in Panyula Village, Bone Regency, using Riffaterre's semiotic theory through hypograms. The type and design of this research are descriptive and qualitative. The data in this study are paqjappi used in traditional Bugis medicine in Panyula Village. Riffaterre's semiotic theory is used to dissect the paqjappi text to describe the meaning contained in paqjappi. The results of the analysis based on the hypogram of the paqjappi text found eight Islamic metaphorical paqjappi mantras, including the words Bismillahirahmanirahim, La Ilaha Illallah, Kun Fayakun, and Muhammadarrasulullah. This shows that the text has undergone a combination of Panyula community traditions and Islamic teachings. There are names in Paqjappi that have intermediaries or signs, namely, angel and prophet (Prophet Muhammad Saw). Angels and prophets (Prophet Muhammad Saw) are considered intermediaries in praying to Allah SWT. Then the paqjappi text expresses hope for healing.